Anticancer Activity of Natural Flavonoids: Inhibition of HIF-1α Signaling Pathway - Deng, Xiangping; Peng, Yijiao; Zhao, Jingduo; Lei, Xiaoyong; Zheng, Xing; Xie, Zhizhong; Tang, Guotao (Current Organic Chemistry, 2019)
Rapid tumor growth is dependent on the capability of tumor blood vessels and glycolysis to provide oxygen and nutrients. Tumor hypoxia is a common characteristic of many solid tumors, and it essentially happens when the growth of the tumor exceeds the concomitant angiogenesis. Hypoxia-inducible factor 1 (HIF-1) as the critical transcription factor in hypoxia regulation is activated to adapt to this hypoxia situation. Flavonoids, widely distributed in plants, comprise many polyphenolic secondary metabolites, possessing broadspectrum pharmacological activities, including their potentiality as anticancer agents. Due to their low toxicity, intense efforts have been made for investigating natural flavonoids and their derivatives that can be used as HIF-1α inhibitors for cancer therapy during the past few decades. In this review, we sum up the findings concerning the inhibition of HIF-1α by natural flavonoids in the last few years and propose the idea of designing tumor vascular and glycolytic multi-target inhibitors with HIF-1α as one of the targets.
Keywords: hypoxia situation